Survey of business management factors associated with mixed animal veterinary practice size and growth - Brusk, Amy M. (Kansas State University, 2009)
Recent literature regarding potential shortages of food animal veterinarians has sparked interest in how to improve economic sustainability in this profession. Business management practices influence profitability, but relatively little work has been done evaluating the impact specific practices have on mixed animal veterinary practice growth. The objectives of this research were to determine potential associations between practice management factors and both practice size and practice growth measured over a 5-year period. Results from a cross sectional survey of mixed animal veterinary practitioners (n=54) were analyzed to address these research objectives. Survey participants had practiced a mean of 19.6 years and most (85%) practiced in towns with populations of less than 25,000. Practice size was measured by the 5-year average of number of veterinarians (NV), gross practice income (GPI), and gross income per veterinarian (GPIV). Positive associations were identified among all three measures, and active client communication was associated with higher GPI. Practices employing a business manager were associated with increased GPI and GPIV. Practice growth was measured by the mean percent change in number of veterinarians (NVG), percent growth in income per veterinarian (DVMG), and percent growth in gross income (GRSG). Practice size variables indicate influences of business management practices on the size of veterinary practices while practice growth variables indicate whether the practice has changed in size and how business management practices are associated with those changes. On average, practices exhibited positive growth in NVG (4.4%), DVMG (8.1%) and GRSG (8.5%) during the study period, but the growth rate was highly variable among practices. Practices with a marketing plan exhibited a higher DVMG, while frequency of adjusting prices and pricing structures were associated with higher GRSG. Results from this study provide insight into the associations between specific management techniques and veterinary practice size and growth rate.
Keywords: Agricultural Economics; Business; Management; Marketing; Rural; Veterinary Medicine; Business Administration, General (0310); Business Administration, Management (0454); Economics, Agricultural (0503)